Multiperiodic Pulsations of the Unique DAQ White Dwarf J0551+4135: Insights into a Merger Remnant - Uzundag, Murat (2025)
2MASS J05513444+4135297 (hereafter J0551+4135) is the only pulsating DAQ white dwarf (WD) known with a carbon and hydrogen atmosphere. Its unusual atmospheric composition and kinematics indicate a WD merger origin. We present time-series photometry of J0551+4135 obtained using the Apache Point Observatory 3.5 m, Gemini North 8 m, and Gran Telescopio Canarias 10 m telescopes. J0551+4135 exhibits variations in pulsation amplitude and frequency over time. We detect 10 significant recurring peaks across different subsets of observations, with frequencies ranging from 987 to 1180 μHz, consistent with nonradial gravity (g)-mode oscillations. We present new evolutionary models suitable for spectroscopic characterization of DAQ WDs, and derive a mass of 1.13 ± 0.01M⊙and a cooling age of 1.7 ± 0.1 Gyr for a CO core, and 1.12 ± 0.01M⊙and 1.6 ± 0.1 Gyr for an ONe-core WD, respectively. However, detailed asteroseismology of this unique pulsator has to wait until fully consistent DAQ evolutionary models are available. Further observations, including multisite campaigns to reduce daily aliasing and to improve the signal-to-noise ratio, would be helpful for the identification of additional modes and constraining the internal structure of this unique pulsator.